Oxytocin Reduces Ethanol Self‐Administration in Mice. (27th March 2017) - King, Courtney E.; Griffin, William C.; Luderman, Lauryn N.; Kates, Malcolm M.; McGinty, Jacqueline F.; Becker, Howard C.
Abstract : Background: Excessive ethanol (EtOH) consumption remains an important health concern and effective treatments are lacking. The central oxytocin system has emerged as a potentially important therapeutic target for alcohol and drug addiction. These studies tested the hypothesis that oxytocin reduces EtOH consumption. Methods: Male C57BL/6J mice were given access to EtOH (20% v/v) using a model of binge‐like drinking ("drinking in the dark") that also included the use of lickometer circuits to evaluate the temporal pattern of intake as well as 2‐bottle choice drinking in the home cage. In addition, EtOH (12% v/v) and sucrose (5% w/v) self‐administration on fixed‐ and progressive‐ratio schedules were also evaluated. A wide range of systemically administered oxytocin doses were tested (0 to 10 mg/kg) in these models. Results: Oxytocin (0, 0.3, 1, 3, or 10 mg/kg) dose dependently reduced EtOH consumption (maximal 45% reduction) in the binge drinking model, with lower effective doses having minimal effects on general locomotor activity. Oxytocin's effect was blocked by pretreatment with an oxytocin receptor antagonist, and the pattern of contacts (licks) at the EtOH bottle suggested a reduction in motivation to drink EtOH. Oxytocin decreased 2‐bottle choice drinking without altering general fluid intake. Oxytocin also reduced operant responding for EtOH and sucrose in a dose‐related manner. However, oxytocin decreased responding and motivation (breakpoint values) for EtOH at doses that did not alter responding for sucrose. Conclusions: These results indicate that oxytocin reduces EtOH consumption in different models of self‐administration. The effects are not likely due to a general sedative effect of the neuropeptide. Further, oxytocin reduces motivation for EtOH at doses that do not alter responding for a natural reward (sucrose). While some evidence supports a role for oxytocin receptors in mediating these effects, additional studies are needed to further elucidate underlying mechanisms. Nevertheless, these results support the therapeutic potential of oxytocin as a treatment for alcohol use disorder. Abstract : A series of studies was conducted to examine the effects of the neurohormone oxytocin on alcohol consumption in mice. Results indicated that systemic administration of oxytocin decreased binge‐like alcohol intake in a dose‐related manner (data not shown) and reduced operant oral alcohol self‐administration at doses that did not alter responding for sucrose. These results support an emerging preclinical and clinical literature implicating a potential therapeutic role for oxytocin in alcohol addiction.